In Silico Study to Predict the Potential of Beta Asarone, Methyl Piperonylketone, Coumaric Acid in Piper Crocatum as Anticancer Agents - Abkar, Ahmed Hasan; Djati, Moch. Sasmito; Widodo, Widodo (Graduate School, Universitas Brawijaya, 2021)
Piper Crocatum Ruiz & Pav leaves often be used to treat various diseases, including cancer, empirically. This study aimed to analyze the anticancer activities of Piper Crocatum bioactive compounds via In Silico analysis. The methods were biological activity analysis, cell line cytotoxicity activity, SwissADME, STITCH, molecular docking, and molecular dynamics simulation. The investigated bioactive compounds were Î²-asarone, methyl piperonylketone, and coumaric acid. The results showed the biological activities of the compounds related to anticancer were anti-mutagenic, TNF expression inhibitive, and MMP9 expression inhibitive. The prediction of cytotoxicity analysis results showed that investigated bioactive compounds were toxic on various tumor cell lines. Based on swissADME results, almost all compounds have good pharmacological properties, except coumaric acid. Docking analysis demonstrated the presence of bioactive compounds inhibited TNFa, HER2, and MMP9 as the target protein. The molecular dynamic result was confirmed using molecular dynamic and it shows that β-asarone interaction was stable against MMP9 and TNF protein showed by the low RMSD value. The study found the investigated bioactive compounds of Piper crocatum have the activity of anti-cancer via the inhibition of TNFa and MMP9 protein. However, further research still needs to be done to confirm the prediction results of this In Silico study. Keywords: anticancer, In Silico, molecular docking, Piper crocatum.